Straddling Across Religious Borders: The Case of the Muslim Jogis - Singh, Mukesh Kumar (Journal of the American Academy of Religion, 2025)
Muslim Jogis constitute a unique community that straddles the boundaries of Islam, Hinduism, and the Nath Yogi (Jogi) order dwelling at the margins of religion, sect, and caste. By self-definition they identify as a caste of Yogis (vernacular term, Jogis), followers of god Shiva in belief, and Muslims in religious identity. While located at the cusp of cultural and religious zones of Hinduism and Islam, they traditionally performed the roles of healers, bards, ritual specialists, and folklorists in north Indian village society catering to a variety of villagers' needs, including the ability to cure various diseases with their yogic skills. This article examines the meaning and image of the Muslim Jogi to understand a dynamic interplay between various religious traditions, belief systems, and popular religious practices complicating and challenging the imaginary of Jogis (Yogis) as quintessentially a Hindu idea. It shows a long tradition of Muslim Jogis in north Indian village society who used their yogic skills in everyday life, arguing that lived religious practices and the yogic knowledge of the Muslim Jogis, which drew on yogic culture, popular magico-Tantric beliefs, and Islam, are representative of shared and localized forms of Tantric and yogic traditions.